The Role of Attitudes toward Local Product in Green Marketing Strategy: Evidence from Muslim Consumers - M Qoshid Al Hadi; Iman Setya Budi (International Journal of Islamic Economics and Finance (IJIEF), 2022)
The impact of the COVID-19 pandemic has increasingly aroused the awareness of companies towards environmental issues. The company began to make changes in energy utility to reduce environmental impacts, including its marketing pattern. In addition, the issue of the government's campaign to love local products has also influenced consumer purchase intention. For this reason, this study aims to examine the impact of green marketing strategy (GMS) variables, which are green advertising and green brand image, and the attitudes toward local products as the moderating role, on Muslim purchase intention. This study used the partial least square–structural equation modeling (PLS-SEM) method. The data collected from 89 Muslim consumers in Banjarmasin, Indonesia, were processed using SmartPLS. This study uncovered that both GMS variables significantly affected the consumers’ purchase intention. However, this study also found that the attitude toward local products did not moderate the relationship between the two previous variables on purchase intention, but it significantly affected consumers’ purchase intention directly.